Identifikasi dan Prevalensi Ektoparasit Pada Ikan Betok (Anabas testudineus) di Kawasan Wisata Air Hitam Perairan Kereng Bangkirai Kota Palangka Raya - Rozik, Mohamad; Maryani, Maryani; Rivaldo, Rivaldo (Universitas Batangahari Jambi, 2024)
This study aims to identify ectoparasites and analyze the level of prevalence, intensity of attacks, and dominance of ectoparasites that attack parrotfish (Anabas testudineus). Sampling was carried out 5 times a week for 20 working days with as many samples as the catch from 3 stations. Primary data was obtained by recording the results of observations. The identification results found three types of ectoparasites including, Trichodina sp, Gyrodactylus sp., and Dactylogyrus sp. The prevalence rate of Trichodina sp. ectoparasites. in the upper reaches of 85.71% with moderate infection rates, and Dactylogyrus sp. 57.14% with a Very Frequent attack rate. In the Middle section the prevalence rate of the ectoparasite Trichodina sp. is 50% with a Very Frequent attack rate and Dactylogyrus sp. 7% with a Moderate attack rate. In the downstream section, the prevalence rate of the ectoparasite Trichodina sp. is 78.94% with a moderate attack level, Dactylogyrus sp. 68.42% with very frequent attacks, and Gyrodactylus sp. 10.52% with Frequent attack rate. Results Intensity of attack by ectoparasites Trichodina sp. in the upper reaches 18.83 ind/head with Moderate infection rate and Dactylogyrus sp. 4 ind/head with low infection rate. In the middle part of Trichodina sp. 40 ind/head with Moderate infection level and Dactylogyrus sp. 7.66 ind/head with moderate infection rate. In the Lower Trichodina sp. 32.86 ind/head with Moderate infection level, Dactylogyrus sp. 5.23 ind/head with low infection rate, and Gyrodactylus sp. 1 ind/head with low infection rate. The largest dominant ectoparasites are Trichodina sp. with a value of 85.20%, Dactylogyrus sp. with a value of 14.46%, and Gyrodactylus sp. with a value of 0.22%.